Fenomena "Phubbing" pada Generasi Z di Social Media - Kylla Rizkia Rahma Putri; Maman Chatamallah (Bandung Conference Series: Communication Management, 2024)
Abstract. Smartphones are something that is inherent in every individual. Smartphone use is increasing from year to year. One of the social phenomena resulting from smartphone addiction is the phubbing phenomenon. Conceptually, "phubbing" is a behavior caused by addiction to smartphones which makes phubbers ignore the person they are talking to when interacting. Problems arise when interaction and communication become ineffective due to phubbing behavior. This research aims to determine the because of motive and in order to motive of phubbing behavior in generation Z students of the Bandung City Social Welfare Polytechnic. This research uses a phenomenological research method with a qualitative approach. The data collection techniques used by researchers are interviews, observation and documentation. The results of this research are: Because of the motives for this phubbing behavior are (1) a feeling of discomfort towards the person you are talking to, (2) students' entertainment needs lie in the smartphones they own, (3) students' personal characteristics cannot be separated from smartphones. , (4) there are urgent activities that need to be carried out and become a distraction for students to carry out phubbing behavior. Meanwhile, the order to motive for this phubbing behavior is to (1) move away from feeling uncomfortable when interacting, (2) move away from feeling bored, (3) fulfill the need for smartphones, (4) don't want to miss out on information on social media. and don't want to miss important things on your smartphone. Abstrak. Smartphone merupakan suatu hal yang sudah melekat pada setiap individu. Penggunaan smartphone kian meningkat dari tahun ke tahun. Salah satu fenomena sosial akibat kecanduan smartphone ialah fenomena phubbing. Secara konsep “phubbing” merupakan perilaku yang dikarenakan adiksinya terhadap smartphone yang menjadikan phubber mengacuhkan lawan bicara saat sedang berinteraksi. Permasalahan timbul ketika interaksi dan komunikasi menjadi tidak efektif dikarenakan perilaku phubbing. Penelitian ini bertujuan untuk mengetahui because of motive dan in order to motive perilaku phubbing pada mahasiswa generasi Z Politeknik Kesejahteraan Sosial Kota Bandung. Penelitian ini menggunakan metode penelitian fenomenologi dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan peneliti adalah wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah: Because of motive dari perilaku phubbing ini ialah (1) adanya rasa ketidaknyamanan terhadap lawan bicara, (2) kebutuhan hiburan para mahasiswa terletak di smartphone yang mereka miliki, (3) karakter pribadi mahasiswa yang tidak bisa lepas dari smartphone, (4) adanya aktivitas mendesak yang perlu dilakukan dan menjadi distraksi mahasiswa untuk melakukan perilaku phubbing. Sedangkan in order to motive dari perilaku phubbing ini ialah untuk (1) peralihan dari rasa ketidaknyamaan saat berinteraksi, (2) peralihan dari rasa jenuh, (3) memenuhi rasa kebutuhan yang ada pada smartphone, (4) tidak ingin tertinggal informasi di social media dan tidak ingin melewatkan hal penting yang ada dalam smartphone.